A Study on the Colors of Traditional Blongket Weaving Fabric at Griya Kain Tuan Kentang, Palembang City - Febiola, Natasya Anggia; Yuliarma, Yuliarma (LPPM Institut Seni Indonesia Padangpanjang, 2024)
Each woven product from various regions has its own uniqueness, because it comes from a different source of ideas. One example is Blongket weaving, which has unique characteristics. The most prominent feature in this study is the type of color and color combination in the Blongket woven fabric which is processed with a limar technique that makes a variety of colors. Until now, the uniqueness of the type of color and the combination of colors with the process of being smeared has not been widely known by the public in general. This study aims to study the types of colors and color combinations in Blongket weaving in Griya Kain Tuan Kentang. This research method uses a qualitative research method that requires informants, with data collection techniques namely interviews, observations, and documentation. The results of this study found 1) The types of colors in model 1 fabric were found in 5 colors including purple, white, green, gold, and brown. On the model 2 fabric, 5 colors were found including blue, pink, yellow, dark blue, and green. On the model 3 fabric, 6 colors were found including green, brown, dark blue, blue, purple, and white. 2) Color combinations in this study found tetrad color combinations